Просторова задача контакту шаруватої основи з підкріплюючим елементом - Кагадій, Тетяна Станіславівна; Kagadiy, Tatiyana; Шпорта, Анна; Shporta, Anna; Білова, Оксана Вікторівна; Belova, Oksana; Білова, Юлія Олексійовна; Belova, Julya; Щербина, Ірина Володимирівна; Sсherbіna, Irina (Херсонський національний технічний університет, 2020)
Розглянуто осесиметричну контактну задачу щодо передачі навантаження від стрижня кругового перерізу до еластичного косого поля з циліндричною анізотропією, що складається з двох ортотропних прошарків, сплетених між собою. Сформульовані та досліджені подібні проблеми для випадку, коли матеріал шарів є в'язкопружним. Приведені граничні проходи, завдяки яким перевіряється точність отриманих результатів. The control of the stress-strain state of viscoelastic bodies with cylindrical anisotropy, which consist of numerous layers and are supported by pads, is very important in practice, particularly in construction. The mechanics of anchor rods and foundations on piles remain very important today. The results can also be useful for stress-strain analyses of fibrous composites. The paper deals with a complex spatial axisymmetric contact problem of transferring a load from a circular cross section rod to a viscoelastic body, which consists of two bonded orthotropic layers with cylindrical anisotropy. The law of the contact stress distribution between the stringer and the body, as well as the force in the stringer if it is loaded longitudinally at the end points, is determined.
Spatial problem of contact of the layered base with the reinforcing element
Keywords: асимптотичний метод; asymptotic method; контактна задача; contact problem; в´язкопружне тіло; viscoelastic body; композиційні матеріали; composite materials; стрингер; stringer; циліндрична анізотропія; cylindrical anisotropy